2020
DOI: 10.1371/journal.pone.0241996
|View full text |Cite
|
Sign up to set email alerts
|

Probing cardiomyocyte mobility with multi-phase cardiac diffusion tensor MRI

Abstract: Purpose Cardiomyocyte organization and performance underlie cardiac function, but the in vivo mobility of these cells during contraction and filling remains difficult to probe. Herein, a novel trigger delay (TD) scout sequence was used to acquire high in-plane resolution (1.6 mm) Spin-Echo (SE) cardiac diffusion tensor imaging (cDTI) at three distinct cardiac phases. The objective was to characterize cardiomyocyte organization and mobility throughout the cardiac cycle in healthy volunteers. Materials and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 37 publications
(90 reference statements)
0
25
0
Order By: Relevance
“…In Fig. 4C,D we show how P2S-sketch does not cause any signal loss even in the presence of physiological noise (porcine cardiac data) [32, 63] and ghost artefacts [70, 51], which are ubiquitous in MRI acquisitions. Note that in either case, P2S-sketch strictly only suppresses noise and does not lead to signal loss or smoothing.…”
Section: Resultsmentioning
confidence: 99%
“…In Fig. 4C,D we show how P2S-sketch does not cause any signal loss even in the presence of physiological noise (porcine cardiac data) [32, 63] and ghost artefacts [70, 51], which are ubiquitous in MRI acquisitions. Note that in either case, P2S-sketch strictly only suppresses noise and does not lead to signal loss or smoothing.…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, motion occurring during readout may lead to spatial inconsistency of information contained in low and high spatial frequencies. To date, shortening readout duration by means of parallel imaging or multishot acquisition schemes has allowed for performance of cDTI at spatial resolutions of 1.6 × 1.6 mm 2 and 1.8 × 1.8 mm 2 54,62 . Additionally, lowering the readout bandwidth leads to increased susceptibility to off‐resonance artifacts that may require dedicated treatment 63,64 .…”
Section: Discussionmentioning
confidence: 99%
“…Assuming a T 2 of 60 ms (Reference 65 ) leads to an additional signal attenuation of ≈20%, which needs to be considered. Moulin et al 54 compensated for the prolonged echo time by partial Fourier sampling and an under‐sampling factor of 2 in conjunction with a more powerful gradient system to achieve an echo time of 61 ms (versus 81 ms) for a spatial resolution of 1.6 × 1.6 mm 2 . Our simulation does not consider blurring due to broadening of the point spread function by T2 decay during echo planar imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other in vivo studies [21,22] have also demonstrated that changes in diffusion tensor metrics, such as Fractional Anisotropy (FA), and Apparent Diffusion Coefficient (ADC) agree with late gadolinium enhancement (LGE) imaging and can depict areas with myocardial infarction and tissue remodeling. Despite growing progress in the field of MRI pulse sequences [23][24][25][26], hardware [27] and reconstruction methods [28], clinical in vivo DTI MRI remains limited in spatial resolution and signal to noise ratio (SNR) by clinical field strength, and scan times [29]. In vivo cardiovascular DTI must also take into account combined respiratory and cardiac motions, and compensated for them with a dedicated acquisition scheme [23].…”
Section: Introductionmentioning
confidence: 99%